If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 9 = 9x + 7 Reorder the terms: 9 + 8x = 9x + 7 Reorder the terms: 9 + 8x = 7 + 9x Solving 9 + 8x = 7 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 9 + 8x + -9x = 7 + 9x + -9x Combine like terms: 8x + -9x = -1x 9 + -1x = 7 + 9x + -9x Combine like terms: 9x + -9x = 0 9 + -1x = 7 + 0 9 + -1x = 7 Add '-9' to each side of the equation. 9 + -9 + -1x = 7 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 7 + -9 -1x = 7 + -9 Combine like terms: 7 + -9 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| 6+3x+4x^2+2x^3=0 | | (6-8i)(6+8i)= | | 3(t-5)-t=7 | | 2x+2y=2809.30 | | 2(5x-6)=4[x-3x+30] | | 100x^2-21=110 | | 4(3x-9)-5=4(x-5)+27 | | 4y^3+27y^2+27=0 | | 27y^2+27=0 | | 3-4*6+3= | | 4(3x-8)-5=4(x-5)+15 | | (11x+26)-3= | | Y^6+9y^4-4y^3+27y^2+27=0 | | -7(2c+5)=(c-6) | | 8y-9=12y+15 | | 5x-(2x+4)=14 | | x^2-5x-2.25=0 | | Y=(3x+8)(x-9) | | 6+(3x-4)-(7x+11)= | | 8(7x-6)=27 | | x+20=5x+8 | | x*0.022=1 | | 12y-13=7y+12 | | 4-23=8x-6-7x | | 2(3x)+5x=770 | | 2x+11=21-3x | | 10x=20.2 | | 80=1.8+32 | | 8+2(x-8)=10-6(x-3) | | 7(x-2)+2=7x-2(2-x) | | (6-2x)*5=(x-3)*8 | | f(3x+1)=5*x+2 |